Sub-zero temperature mechanically stable low molecular weight hydrogels - Fayter, Alice E. R. (Royal Society of Chemistry, 2018)

(untitled) (J Mater Chem B)
We show here a low molecular weight hydrogelator based on a functionalised-dipeptide which is stable down to temperatures of –12 °C despite being made from >99% water. This stabilty at low temperature can be extended to ∼–40 °C by gelling water : glycerol mixtures. The temperature range is wider than that of the glycerol : water mixtures alone. The rheological properties of the gels do not change at this low temperature compared to that of gels at 25 °C. This freezing point depression offers a potentially new method of transporting gels and offers the prospect of hydrogels being used at much lower working temperatures whilst retaining the desired rheological properties, this is useful for cryopreservation.